Effect of rehabilitation training based on HT-CHC mode on cognitive ability of children with specific learning disabilities - LUO Dandan, SHEN Min (Xin yixue)
Objective To evaluate the interventional effect of personalized rehabilitation training based on CHC cognitive theory and hypothesis testing CHC （HT-CHC） mode on children with specific learning disabilities （SLD）. Methods In this self-control study， 42 children with SLD who attended the Learning and Dyslexia Clinic of the Pediatric Hospital of Fudan University from January 2021 to January 2023 were selected. After diagnosis， they were assessed for cognitive abilities by the Sensory Integration Developmental Scale， Rapid Naming （Numbers， Figures）， Writing Performance Assessment Scale， No-Motion Visual Perception Test （MVPT-4）， Attention Deficit Checklist. Personalized rehabilitation training plans were formulated according to the assessment results， once a week for 10 sessions. Assessment data were collected pre-intervention and 3 months post-intervention for its own before-and-after control study. Results After the rehabilitation treatment， children with SLD showed significant improvement in sensory integration （vestibular sense， proprioception， and learning ability）， writing performance （neatness， pen grip engineering， and writing direction）， visual-perceptual function （visual discrimination， visual memory， spatial relationship， and visual completion）， rapid naming （rapid naming of numbers and pictures）， and attention compared with the pre-treatment period （all P < 0.05）. Conclusions Targeted rehabilitation training based on the HT-CHC mode can effectively improve the cognitive abilities of children with SLD.